Integrated Marine Management in the United Kingdom Overseas Territories - Hardman, Emily; Thomas, Hannah L.; Baum, Diane; Clingham, Elizabeth; Hobbs, Rhys; Stamford, Tammy; Whomersley, Paul; Smith, Ness (Frontiers in Marine Science, 2022)
Like many small island communities, the United Kingdom Overseas Territories (UKOTs) are directly dependent on their marine resources for a range of ecosystem services, such as income generation, subsistence, leisure, recreation and wellbeing. Healthy marine ecosystems also play a broader role in climate regulation, coastal resilience and habitat provision. With Blue Belt Programme assistance, the UKOTs are developing enhanced protection and sustainable management strategies for their marine environments, using an Integrated Marine Management (IMM) approach. This coordinates cross-sectoral planning and management to carefully balance marine conservation and sustainable use of resources in order to minimize socio-cultural and economic impacts to the local community. We describe the IMM approach taken in two UKOT case studies. In Ascension Island, a conservation planning and resource management process was initiated with an objective to protect at least 50% of Ascension’s waters from commercial fishing, resulting in the designation of one of the largest Marine Protected Areas (MPAs) in the Southern Atlantic. In St Helena, a new licensing framework for marine developments was developed within an existing sustainable use MPA. From these two approaches, we highlight aspects of the process, lessons learned and recommendations that may be useful for other small islands planning to implement IMM, particularly regarding the importance of effective stakeholder engagement, coordination across different governance scales, and long-term financial resources.